(untitled) (Anwer Khan Modern Medical College Journal, 2013)
This case case control study was undertaken to see if there is any association of serum Zinc level with histologically diagnosed prostatic cancer patients. Also to re-establish the importance of estimation of serum Prostate specific antigen PSA, (Total, Free and ratio between free and total) in prostate cancer patients. It was evident from the present study that serum Zinc level has got statistically significant difference between control and prostate cancer patients (p<0.000),. Total PSA and ratio of free and total PSA was also significantly different between control and prostatic cancer patients (p<0.04 and 0.006 respectively). However no significant difference was observed in free PSA level between this two groups (p<0.282). It was concluded from the present study that serum Zinc level could be an adjuvant laboratory test in the diagnosis of prostate cancer and can be started as a routine test in case of suspected prostatic cancer. Also total PSA level and ratio of free and total PSA not free PSA should be done and correlated for diagnosis of prostate cancer. DOI: http://dx.doi.org/10.3329/akmmcj.v4i1.13679 AKMMC J 2013: 4(1): 15-19